First report of the hard tick Ixodes Ricinus on dogs in Lebanon - Darwiche, Walid (Veterinaria Italiana, 2023)
Ixodes ricinus is a hard tick that can infest a large array of hosts. It is mostly abundant in the cool, humid deciduous and coniferous woods and forests of Europe. All I. ricinus life stages are potential vectors of many diseases, most notably Lyme disease, which affects millions of people yearly. Lebanon, an Asian Mediterranean country with mild cool winters and hot dry summers, lacks many reports concerning ticks. A study on tick abundance and identification on dogs presented to veterinary facilities, over the course of the years 2020 and 2021 was done. Several species of ticks were identified, with the least abundant being I. ricinus. To the best of our knowledge, this is the first report of the tick species in the country. More studies on the distribution and abundance of I. ricinus in Lebanon should be made in order to properly estimate the pathogens it carries, and consequently implement the appropriate prophylactic measures concerning public health.